EKSPLORASI PEMANFAATAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN DAYA SAING UMKM PESANTREN DI ERA DIGITAL - Pandary, Pandary Ary Yanti; Romi Adetio Setiawan; Andi Harpepen (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the adoption and implementation of information technology, particularly e-commerce and social media, in improving the competitiveness of Islamic Boarding School MSMEs at the Nurul Qur'an Islamic Boarding School in Lebong Atas District. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of five informants who are managers of Islamic boarding school MSMEs. The results of the study indicate that the use of information technology has a positive impact on expanding marketing reach, increasing revenue, and strengthening the image and uniqueness of Islamic boarding school MSME products. Social media and marketplaces are the main digital marketing tools that are considered easy to use and effective in reaching consumers outside the local area of the Islamic boarding school. However, the use of information technology still faces several obstacles such as limited human resources, low digital literacy, and limited supporting facilities and infrastructure. Therefore, it is necessary to increase human resource capacity and continuous mentoring so that the use of information technology can be optimized as a strategy to increase the competitiveness of Islamic boarding school MSMEs in the digital era.